Alex Reymundo : Red Nexican - Reymundo, Alex.; Montoya, Scott; Moulton, Collin; Knudson, Eric.; Bankhead, Adam.; Funny As Hell Productions; Image Entertainment (Firm) ([United States] : Funny As Hell Productions ; Chatsworth, CA : Distributed by Image Entertainment, 2010)
Irreverent bad boy Alex Reymundo will crack you up with a nonstop stream of hilarious jokes and clever observations.
Videodisc release of a 2009 production.
For special features see interactive menu.
Music, Eric Knudson ; editor, Adam Bankhead.
Alex Reymundo.
Contains explicit language.
DVD, Dolby digital, 5.1 Surrond, NTSC.
Keywords: Reymundo, Alex; Stand-up comedy -- United States; Entertainers -- Performances; Mexican American wit and humor; United States